Desert ants (Melophorus bagoti) oscillate and scan more in navigation when the visual scene changes - Sudhakar Deeti; Ken Cheng (Animal Cognition)
Abstract Solitarily foraging ants learn to navigate between important locations by comparing their current view with memorized scenes along a familiar route. As desert ants, in particular, travel between their nest and a food source, they establish stable and visually guided routes that guide them without relying on trail pheromones. We investigated how changes in familiar visual scenes affect the navigation of the red honey ant (Melophorus bagoti). In Experiment 1, ants were trained to follow a one-way diamond-shaped path to forage and return home. We manipulated scene familiarity by adding a board on their homebound route just before the nest. In Experiment 2, ants were trained to travel a straight path from their nest to a feeder, and we removed the prominent landmarks on the route after they had established a stable route. We predicted that these scene changes would cause the ants to deviate from their usual straight paths, slow down, scan more, and increase their lateral oscillations to gather additional information. Our findings showed that when the familiar scene was changed, ants oscillated more, slowed their speed, and increased scanning bouts, indicating a shift from exploiting known information to more actively exploring and learning new visual cues. These results suggest that scene familiarity plays a crucial role in ant navigation, and changes in their visual environment lead to distinct behavioral adaptations aimed at learning about the new cues.